Sugammadex-Enhanced Neuronal Apoptosis following Neonatal Sevoflurane Exposure in Mice - Maiko Satomoto (Anesthesiology Research and Practice, 2016)
In rodents, neonatal sevoflurane exposure induces neonatal apoptosis in the brain and results in learning deficits. Sugammadex is a new selective neuromuscular blockade (NMB) binding agent that anesthesiologists can use to achieve immediate reversal of an NMB with few side effects. Given its molecular weight of 2178, sugammadex is thought to be unable to pass through the blood brain barrier (BBB). Volatile anesthetics can influence BBB opening and integrity. Therefore, we investigated whether the intraperitoneal administration of sugammadex could exacerbate neuronal damage following neonatal 2% sevoflurane exposure via changes in BBB integrity. Cleaved caspase-3 immunoblotting was used to detect apoptosis, and the ultrastructure of the BBB was examined by transmission electron microscopy. Exposure to 2% sevoflurane for 6 h resulted in BBB ultrastructural abnormalities in the hippocampus of neonatal mice. Sugammadex alone without sevoflurane did not induce apoptosis. The coadministration of sugammadex with sevoflurane to neonatal mice caused a significant increase (150%) in neuroapoptosis in the brain compared with 2% sevoflurane. In neonatal anesthesia, sugammadex could influence neurotoxicity together with sevoflurane. Exposure to 2% sevoflurane for 6 h resulted in BBB ultrastructural abnormalities in the hippocampus of neonatal mice.